2016
DOI: 10.1159/000443407
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Deep Brain Stimulation Lead Targeting Accuracy and Procedure Duration between 1.5- and 3-Tesla Interventional Magnetic Resonance Imaging Systems: An Initial 12-Month Experience

Abstract: Background: Interventional magnetic resonance imaging (iMRI) allows deep brain stimulator lead placement under general anesthesia. While the accuracy of lead targeting has been described for iMRI systems utilizing 1.5-tesla magnets, a similar assessment of 3-tesla iMRI procedures has not been performed. Objective: To compare targeting accuracy, the number of lead targeting attempts, and surgical duration between procedures performed on 1.5- and 3-tesla iMRI systems. Methods: Radial targeting error, the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Furthermore, the increased error in our MER group for the right lead suggests that greater brain shift occurs over the course of the surgical case, as the left lead was always placed first. Our iMRI accuracy was similar to other iMRI studies ( 10 , 38 , 39 ), and was superior to results for CT-based verification approaches, which report mean errors of approximately 1.2 mm (SD = 0.7 mm) ( 11 , 12 ). The greater accuracy of iMRI is likely a product of prospective stereotaxy, as unlike CT-based approaches, the trajectory can be adjusted prior to placement to account for brain shift.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the increased error in our MER group for the right lead suggests that greater brain shift occurs over the course of the surgical case, as the left lead was always placed first. Our iMRI accuracy was similar to other iMRI studies ( 10 , 38 , 39 ), and was superior to results for CT-based verification approaches, which report mean errors of approximately 1.2 mm (SD = 0.7 mm) ( 11 , 12 ). The greater accuracy of iMRI is likely a product of prospective stereotaxy, as unlike CT-based approaches, the trajectory can be adjusted prior to placement to account for brain shift.…”
Section: Discussionsupporting
confidence: 85%
“…The main difference between asleep and awake DBS surgery is the method of intraoperatively verifying the position of electrode implantation. Some neurosurgical centers have performed asleep DBS surgery under GA with iMRI 4 , 8 , 9 or iCT merged together with preoperative MRI to verify the accuracy of electrode implantation 10 , 11 . It has been demonstrated that the clinical outcomes and complication rates of asleep surgery are comparable to those in historical studies using MER to guide or confirm lead placement under LA 12 – 15 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, awake surgery has been typically performed with intraoperative test stimulations 3 . Recently, asleep surgery has been performed under general anesthesia (GA) with intraoperative magnetic resonance imaging (iMRI) 4 or computed tomography (iCT) 5 to confirm the position of the electrode tip. However, limited research and clinical experience has been reported regarding robot-assisted asleep surgery.…”
Section: Deep Brain Stimulation (Dbs) Surgery Is An Effective Treatmementioning
confidence: 99%
“…Thus, to balance visibility, measurement accuracy, familiarity for many users, and broad applicability, we selected the T2 ∗ sequence, which is similar to the frequently used T2 sequence and has moderate susceptibility weighting capabilities. In addition, the 3T MRI used in the present study with or without frames may be better for visualization and direct targeting of DBS than is stereotactic 1.5T MRI (Cheng et al, 2014; Southwell et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…However, MRI sequences with worse quality cannot be used. Worse MRI image contrast due to lower magnetic field (Cheng et al, 2014; Southwell et al, 2016), 1-mm thickness T2 slicing, and higher noise from metal artifacts or any cause (O’Gorman et al, 2011) can result in a lower contrast-to-noise ratio, which is not suitable for machine learning algorithm application.…”
Section: Discussionmentioning
confidence: 99%